(untitled) (Pixel :Jurnal Ilmiah Komputer Grafis, 2026)
This study analyzes the design elements and visual semiotics of Instagram content on the @disparekrafpora_gorontaloprov account owned by the Department of Tourism, Creative Economy, Youth, and Sports of Gorontalo Province as a visual communication medium in building regional tourism identity. The research employs a descriptive qualitative approach with Roland Barthes’s semiotic method across three levels of meaning: denotation, connotation, and myth. The research objects are visual content on the Instagram account with 1,989 posts and 5,643 followers as of May 2026, selected purposively based on natural destination photos, promotional infographics, and cultural/religious content categories. Analysis focuses on design elements including typography, color, layout, and photography. Results indicate that the content consistently uses a green-white color palette representing Gorontalo’s nature, bold sans-serif typography projecting modernity, and destination photography (beaches, waterfalls, whale sharks, Baiturrahim Mosque) forming mythological narratives of Gorontalo as a hidden paradise and ’Serambi Madinah’ of Sulawesi. These design elements work synergistically to build Gorontalo’s tourism identity in digital space.